Assessing the utilization of young-age falcata [falcataria moluccana (Miq.) Barneby & J.W. Grimes] for veener production - Alipon, Marina A.; Bondad, Elvina O.; Lantican, Carl Anthony A.; Gilbero, Dennis M.; Jimenez, Juanito P. Jr (Philippine journal of science)
"This paper presents the mechanical properties, veneer recovery including the cost benefits, pf 3-, 5-, and 7-year old falcata [Falcataria moluccana (Miq.) Barneby & J.W. Grimes] for veneer production. Mechanical properties covered modulus of rupture (MOR), stress at the proportional limit, and modulus elasticity (MOE) in static bending; compression parallel- and perpendicular-to-grain; shear; and hardness and toughness. The study was conducted to evaluate the effects of age on these properties and the cost-benefits of converting the species at different ages, and to recommend the optimum age and price for the utilization of the species for veneer production" - title page.